(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The problem of health of the children’s population of Ukraine has become particularly relevant in recent decades, because, despite a number of developed and implemented state and regional programs to preserve and strengthen the health of the population, there remains a high incidence of children, their mortality rate of under one year, which determines the need to identify factors for the formation of children’s health. In the article summarized authors’ approaches to the definition of factors influencing the level of health and the peculiarities of its formation in the children’s population. It has been revealed that the classical approach identifies all the factors affecting the health of people, including the children, with factors related to the way of life; biological factors; factors related to the state of the environment (environmental factors) and medical factors. Logically, they can be divided into favorable (wellness) and unfavorable (risk factors). At the same time, risk factors can be distinguished according to the age of the infant population: in the period of pregnancy and childbirth, in the period of early childhood, and factors reflecting the conditions and lifestyle of children. Here, in our opinion, it is expedient to allocate even so-called school risk factors, which operate continuously, prolonged and systematic, since 11 of the 17 years of life the child carries out precisely in the school environment. On the basis of the conducted research the author’s vision of the classification of the factors of formation of the health of the children population was presented. The following features of the classification were distinguished: the content (socio-economic, environmental, medical and socio-political), the direction of influence (favorable and unfavorable), the duration of impact (short- and long-term impact), the mode of influence (direct and indirect impact), the level of occurrence (macro-, meso- and microfactors). It was worth noting that all factors (socio-economic, environmental, medical, and socio-political) are interconnected and mutually reinforcing each other, both in a positive and a negative direction, therefore it is expedient to determine their influence on the formation of the health of the children’s population by calculating the integral index